2015
DOI: 10.1002/jppr.1085
|View full text |Cite
|
Sign up to set email alerts
|

Don't rush to crush: audit of modification to oral medicines for patients with swallowing difficulties

Abstract: Background Oral medicines are frequently modified prior to administration for patients with swallowing difficulties or enteral tubes. The current Australian guideline, the Don't Rush to Crush ( DRTC ) Handbook has been available since 2011, and this study compares practice with its recommendations. Aim To assess compliance with Australian guidelines for the preparation of medications in patients who are unable to swallow solid oral medicines, and to provide nursing education as necessary to improve practice. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Two intervention studies assessed nurse knowledge both before and after an education and training intervention . One of these studies that aimed to improve knowledge and drug administration in SI patients reported an overall increase in knowledge scores, including identification of MR codes (0–40%), and an increase from 51% to almost 90% for knowledge relating to the purpose and consequences of crushing MR preparations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two intervention studies assessed nurse knowledge both before and after an education and training intervention . One of these studies that aimed to improve knowledge and drug administration in SI patients reported an overall increase in knowledge scores, including identification of MR codes (0–40%), and an increase from 51% to almost 90% for knowledge relating to the purpose and consequences of crushing MR preparations.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists (75%), nurses (37%) and GPs (34%) correctly identified that certain drugs (in this case azathioprine) can cause harm to the administrator, but few participants identified that modifying antibiotics can also constitute a risk to the administrator. Overall, knowledge levels were found to vary greatly within the nursing profession, as well as between nurses, pharmacists and doctors …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations